Kontribusi Media Powerpoint Interaktif dan Model Problem Based Learning terhadap Hasil Belajar IPAS SDN 2 Kalanglundo - Nadhia Pristy; Sukartono (Jurnal Elementaria Edukasia, 2023)
The learning outcomes of grade IV students have not shown the expected results. This is because learning tends to be teacher-centred. This study aims to determine the learning outcomes of grade IV students of SDN 2 Kalanglundo Grobogan through  Interactive Powerpoint media and Problem Based Learning learning models. This type of research is quantitative, with an ex-post facto design. The population of this study was all grade IV students of SDN 2 Kalanglundo, Ngaringan sub-district, totaling 40 students. The sample of this study amounted to 36 students using the Probability Sampling technique. The data collection method is carried out by questionnaire and documentation methods. The result data that have been obtained are analyzed using normality tests, simple linear regression, multiple linear regression, t-test, f-test, coefficient of determination, effective contribution, and relative contribution. The results of the study showed 1) Interactive Powerpoint learning media had a significant effect on learning outcomes, with tcount = 3.598 > ttable = 2.02. 2) The Problem Based Learning learning model  has a significant effect on learning outcomes, with the results of the t test, showing that the value if tcalculate = 3.519 > ttable = 2.10. 3) There is a joint influence between Powerpoint  learning media Interactive and Problem Based Learning learning model  on learning outcomes, with the results of Fcalculate = 10.014 > Ftable = 3.19.